Perceptions of asthma and exercise in adolescents with and without asthma. (3rd August 2018) - Winn, C. O. N.; Mackintosh, K. A.; Eddolls, W. T. B.; Stratton, G.; Wilson, A. M.; Rance, J. Y.; Doull, I. J. M.; McNarry, M. A.; Davies, G. A.
ABSTRACT: Objective : To elicit the views of adolescents, with and without asthma, about exercise and asthma, and the perceived benefits of and barriers to participation. The adolescent views elicited would subsequently inform the design of a high-intensity exercise intervention to improve asthma control. Methods : Fifty-four adolescents (age 13.1 ± 0.9 years; 26 with asthma) participated in twelve semi-structured group interviews. Questions were structured around knowledge, attitudes and beliefs towards asthma and its impact on exercise participation and lifestyle. The interviews were transcribed verbatim, thematically analysed and presented via diagrams of emergent themes. Ethical approval was granted by the institutional research ethics committee. Results : Fear of an asthma attack emerged as the main barrier to exercise, with many adolescents with asthma withdrawing from exercise as a coping strategy; many healthy adolescents perceived this withdrawal as laziness or an excuse. Despite this, the majority (81%) of adolescents with asthma reported exercise to be their most enjoyable activity. Adolescents suggested incorporating mixed activities, such as team games (e.g., rounders, football, netball), for future interventions to ensure adherence. Conclusions : Whilst exercise is important in the management of asthma, the tendency of those with asthma to withdraw from exercise to avoid adverse events could be addressed through a games-based high-intensity exercise intervention. Furthermore, educating all adolescents on asthma could simultaneously reduce stigmatisation and enhance exercise engagement.